A Decrease in Hypoxic Pulmonary Vasoconstriction Correlates With Increased Inflammation During Extended Normothermic Ex Vivo Lung Perfusion. Issue 3 (20th December 2017) - Himmat, Sayed; Alzamil, Almothana; Aboelnazar, Nader; Hatami, Sanaz; White, Christopher; Dromparis, Peter; Mengel, Michael; Freed, Darren; Nagendran, Jayan
Abstract: Normothermic ex vivo lung perfusion (EVLP) is an evolving technology to evaluate function of donor lungs to determine suitability for transplantation. We hypothesize that hypoxic pulmonary vasoconstriction (HPV) during EVLP will provide a more sensitive parameter of lung function to determine donor lung quality for lung transplantation. Eight porcine lungs were procured, and subsequently underwent EVLP with autologous blood and STEEN solution for 10 h. Standard physiologic parameters including dynamic compliance, peak airway pressure, and pulmonary vascular resistance (PVR) remained stable ( P  = 0.055), mean oxygenation (PO2 /FiO2 ) was 400 ± 18 mm Hg on average throughout perfusion. Response to hypoxia resulted in a robust increase in PVR (ΔPVR) up to 4 h of perfusion, however the HPV response then blunted beyond T6 ( P  < 0.01). The decrease in HPV response inversely correlated to cytokine concentrations of Interleukin‐6 and tumor necrosis factor‐α ( P  < 0.01). Despite acceptable lung oxygenation and standard physiologic parameters during 10 h of EVLP, there is a subclinical deterioration of lung function. HPV challenges can be performed during EVLP as a simple and more sensitive index of pulmonary vascular reactivity.